ENT 530 : Case Study: Zureen Collections / Nur Hasanah Mohamad Khizam ... [et al.] - Mohamad Khizam, Nur Hasanah; Ismail, Nur Fatiha Hanum; Ab Aziz, Nur Amira Najwa; Yusof, Maizatul Atiqah; Azhar, Rabiatul Balqis (2021)
This case study has focused on the areas of small business and existing businesses to identify problems or issues that occur in the business. To meet the requirements of this case study, we chose a business that is in the field of beauty that is Zureen Collections. Zureen Collections has a boutique that sells various types of baju muslimah, tudung, complete equipment to perform Hajj and Umrah and many more services that they provide. The founder of this boutique is Mrs Sazureen. He started this business in 2004. This business is a partnership type. The reason why we chose this Zureen Collections is as we want to know what problems will and that have been faced by these small traders. The next reason, the founder of this boutique was an aunt to our friend, so it was easy for us to interact with her. In addition, Zureen Collections also has strengths, weaknesses, threats faced by the company and opportunities in their business. In fact, every business is definitely having strengths, weaknesses, opportunities and threats (SWOT). According to Mrs Sazureen, the factor which makes the strength of their business is to have their own brand, sell muslimah goods, sell orchid arrangements, affordable prices and have a strategic location. Otherwise, they also have weaknesses in their business namely lack of knowledge in social media and also lack of advertising. Zureen Collections found their opportunity to do business by getting high sales during the opening of the school and also during the Hajj and Umrah seasons. Mrs Sazureen also felt threatened by external threats such as competition from instafamous, competition to brands that are already known to the public and also environment and government regulations. Not only that, during the COVID-19 Pandemic, Zureen Collections faced problems in obtaining new materials from suppliers. This is because most of the fabrics used by Mrs Sazureen are from China. The failure to procure a supply of new fabrics made it impossible for the business to produce new products in large quantities. However, during the course of COVID-19, Mrs Sazureen has introduced her new work by selling orchid compositions. This is because a supply of orchids that are still fresh is easy to obtain. And it got a good response from the public. Owners should know how to manage their business to maintain performance and ensure that the business can survive for a long time and thrive and can open many branches everywhere. As a successful entrepreneur, they should be prepared for all the possibilities and problems that will occur in the business. And they believe in one principle that every problem must have a solution whether it is easy or difficult.